Activated carbons from waste Cassia bakeriana seed pods as high-performance adsorbents for toxic anionic dye and ciprofloxacin antibiotic remediation. (December 2021) - Theamwong, Nidchakarn; Intarabumrung, Wimonsiri; Sangon, Suwiwat; Aintharabunya, Suphattra; Ngernyen, Yuvarat; Hunt, Andrew J.; Supanchaiyamat, Nontipa
Graphical abstract: Highlights: Graphitic porous carbons have been prepared from Cassia bakeriana seed pods. KOH activation yielded a carbon with a high proportion of aromaticity. KOH activated carbon exhibited a high adsorption capacity (970 mg/g) for congo red. The adsorption capacity is among the highest reported values for carbon materials. The carbon also showed a high adsorption capacity for ciprofloxacin at 600 mg/g. Abstract: Waste Cassia bakeriana seed pods were used for porous carbon production in a facile pyrolysis process. The carbons were highly efficient adsorbents for methylene blue, congo red and ciprofloxacin antibiotic from aqueous media. The experimental results demonstrated that despite moderate surface area of 283.4 m 2 /g, KOH activated carbon (PSAC-KOH) exhibited the highest adsorption capacity for congo red reported to date for carbon-based adsorbents (970 mg/g). PSAC-KOH also demonstrated a high adsorption capacity at 600 mg/g for ciprofloxacin. Raman spectroscopy, X-ray diffraction and X-ray Photoelectron spectroscopy analysis of the carbons demonstrated an extensive graphitic characteristic, while Fourier transform infrared spectra of PSAC-KOH suggested a high proportion of aromaticity which promotes adsorption mechanisms including electrostatic and π-π interactions. Pseudo-second-order kinetic model fitting suggested a rate-controlling chemisorption mechanism. The utilization of waste Cassia bakeriana seed pods for carbon production may create new opportunities to develop sustainable and highly efficient adsorbents for water remediation.